Effects of Pay-For-Performance on Prescription of Hypertension Drugs among Public and Private Primary Care Providers in Sweden - Lina Maria Ellegård (Lund University, School of Economics and Management, Department of Economics, 2018)
This study exploits policy reforms in Swedish primary care to examine the effect of pay-for-performance (P4P) on compliance with hypertension drug guidelines among public and private health care providers. Providers in regions with P4P are compared to providers in other regions in a difference-in-differences analysis using data from the Swedish Prescription Register for the period 2005-2013. The results indicate that P4P improved guideline compliance regarding prescription of Angiotensin Converting Enzyme (ACE) inhibitors and Angiotensin Receptor Blockers (ARB). The effect is mainly driven by private providers, suggesting that policy makers should take ownership into account when designing incentives for health care providers.
Keywords: D23; H73; I11; I18; J33; 330; Pay-for-performance; Hypertension treatment; Ownership; Primary health care